Recurrent idiopathic pulmonary hemosiderosis after long-term remission presented with Sjogren's syndrome: Idiopathic no more? - Toyoshi Yanagihara; Yuzo Yamamoto; Naoki Hamada; Kunihiro Suzuki; Saiko Ogata-Suetsugu; Eiji Harada; Tetsuzo Tagawa; Minako Fujiwara; Mikiko Hashisako; Junya Fukuoka; Yoichi Nakanishi (Respiratory Medicine Case Reports, 2018)
We report a case of recurrent idiopathic pulmonary hemosiderosis after a long-term remission presented with Sjögren's syndrome. The patient was diagnosed with IPH due to repeated pneumonia and blood sputum in his childhood. He was admitted to our hospital due to exertional dyspnea and dry cough with bilateral ground-glass opacity in chest computed tomography at the age of 32. Video-assisted thoracoscopic surgery was performed and the specimens showed nonspecific interstitial pneumonia pattern with diffuse, chronic alveolar hemorrhage, suggesting recurrence of IPH. He was also diagnosed with Sjögren's syndrome. Further immunological studies will reveal the pathogenesis of IPH. Keywords: Idiopathic pulmonary hemosiderosis, Sjögren's syndrome